(untitled) (Medico Legal Update, 2019)
Objectives: To find the correlation of manner of death with histopathological changes in fatal burns in a tertiary care hospital in north India. Method: This was a comparative study. Cases were thoroughly studied usingspecially designed proforma that included the demographic profile of deceased along with information gathered from relatives, police & hospital records and autopsy findings. Before taking the lung sample, proper consent was taken from the relatives after explaining the purpose of the study. After gross examination, sections were taken from different lobes of lungs. Results: Tracheal congestion was found mainly in accidental deaths (49.77%), followed by suicidal deaths with 28.57% and homicidal deaths with 21.66%. This difference was found to be statistically significant (p<0.001). Lung Consolidation was more commonly seen in accidental and suicidal deaths (48.4%) as compared to homicidal deaths (3.19%). Various other variables were also correlated with type of burns. Conclusion: This association of histopathological changes in lung tissue could help to ascertain the mode of Death, as well as can hint towards conduction of proper inquest in suspicious cases of so called suicidal deaths